STUDI BEDA PROPORSI PUPUK-TANAH- LIMBAH INDUSTRI BAJA "STEEL SLUG" TERHADAP PERUBAHAN CIRI KIMlA TANAH DAN PERTUMBUHAN TOMAT - -, Siswanto; Mindari, Wanti (MAPETA, 2008)
Exploiting of Industrial disposal steel "Steel Slug" for plant media to hang in doubt because obstetrical height of Fe make poison for crop though height Ca and Mg have an effect on positive at crop growth. Research designed to study type proportion fertilize (NPK, Cotton Seed (CS), Compost (C), and Manure (M», soil, and" Steel Slug from '112 5 until 4/2/5 in degrading Fe of through forming Fe-80 complex( chelat+Fe), change pH, N, Ca, Mg, KTK at Entisol 3-7 WAI (Weeks After Incubation), and also the tomato Crop growth old age 35 DAP (Days After Planting). Result of attempt indicate that proportion of fertilizerlsoil/"Steel slug 1 - 4/2/5 Steel Slug" manifestly degrade soil pH that is 1.30,1.63,0.73,0.6 set of, successively for treatment at 5 WAI, and N-Total Mean mount reality equal to 0.48, 0.65, 0.83 and 0.55 for NPK, CS, C and Manure. Obstetrical of Ca at 3 MSI and 5 MSl, lowered by 25.00 me/ 100 g ( NPK 2/2/5), 221.50 me/100 g ( KP 1/2/5). KTK Land.Ground mount mean of equal to 58% ( 5 MSI) and 16% ( 7 MSI). downhill Ion Ferro very real at  5 MSI mean 45% and 7 downhill MSI of mean 30%. While dry weight of crop old age 35 DAP do not show real influence Keyword: "Steel Slug", type fertilize, soil, soil chemical